Estilos de aprendizaje y la creatividad en niños de cinco años de la Institución Educativa Inicial N° 671 Los Paucarcitos San José de Samaria, Nauta 2022 - Costa Torres, Elida (2023)
The objective of this study was to demonstrate the relationship between learning styles and their relationship with creativity in 5-year-old children from the initial educational institution no. 671 "Los Paucarcitos" San José de Samiria, Nauta2022. The study is relational because it observes and describes the relationship between learning styles and creativity of children, population, the subjects are 76 parents, boys and girls from the initial education institution no. 671 Los Paucarcitos - San José de Samiria, Nauta 2022. The study sample consisted of 76 parents, boys and girls (enumeration method). Observations and surveys are used as techniques, and observation sheets are used as tools to collect information, which is also validated by experts on the subject. Conclusions There was not a high level of correlation between learning styles and creativity among five-year-old children from the local educational institution "Los Paucarcitos" Nauta San José de Samíria N°671, Nauta 2022.